Dharmapravicaya: aspects of Buddhist studies; essays in honour of N. H. Samtani - Lālajī; Willemen, Charles; Samtani, Narayan Hemandas (Buddhist World Press, 2012)
Narayan Hemandas Samtani, b. 1924, former professor of Buddhist Studies, Banaras Hindu University; contributed articles